Custodial Deaths in Jamnagar Region of Gujarat: A 5-Years Retrospective Study Report - Chaudhari , K; Pithadiya , N R; Rathod , J; Singh , O G (Journal of Indian Academy of Forensic Medicine, 2023)
Twenty cases of custodial deaths were examined retrospectively in the present study. Out of these twenty cases, there were nineteen cases  of males and one case of females. The majority of the cases occurred in the age group of 31-40 years, followed by the 21-30 years age  group. There were 14 cases of natural death in whom the presence of pre-existing diseases was found and 6 cases were of unnatural deaths.  In this study out of 14 natural deaths, 10 cases were of Ischemic heart disease/myocardial infarction with 2 cases of renal failure and 1 case  each of pulmonary tuberculosis and chronic hepatitis. There were 6 cases of unnatural deaths; there were 3 cases of suicidal hanging, 2  cases were of multiple body injuries caused by blunt force, and 1 case of accidental choking due to the aspiration of food material.
Keywords: Custodial death; Natural death; Unnatural death; Police custody